Ankle and Knee Place
This page focuses on Achilles tendinitis, Patellar tendinitis, ACL tears, and Meniscus tears, all of which are injuries common in athletes and dancers. (And, yes, it's also spelled tendonitis--both are correct.) We hope that you can use this web site as one of many resources as you continue learn about how to deal with your injuries. In other words, we are not experts in the field of sports medicine; rather, we are two physically active people who have had injuries and have done lots of research on them and hope that you can benefit from our information and advice in addition to your doctor's. ANKLE Achilles tendinitis Treatment Common causes KNEE Patella tendinitis (Jumper's knee) ACL tear Meniscus tear other pages of related interest: R.I.C.E. Posture and footwear Stretching Bibliography